Assessment of Serum Galactomannan Test Results of Pediatric Patients With Hematologic Malignancies According to Consecutive Positivity and Threshold Level in Terms of Invasive Aspergillosis Diagnosis: Cross-Sectional Research in a Tertiary Care Hospital. Issue 5 (July 2020) - Çağlar, İlknur; Özkerim, Duygu; Tahta, Neryal; Düzgöl, Mine; Bayram, Nuri; Demirağ, Bengü; Karapinar, Tuba H.; Sorguç, Yelda; Gözmen, Salih; Dursun, Vecihe; Oymak, Yeşim; Vergin, Canan; et al.
Abstract : The aim of this study was to evaluate the diagnostic utility of serum galactomannan (GM) positivity for invasive aspergillosis (IA) in children. Positive GM results between January 2015 and August 2017 were reviewed retrospectively in children with hematologic malignancies. Single and consecutive positive GM results were evaluated according to the different galactomannan index (GMI) (>0.5, >0.7, >1.0 and >1.5) values. There were 104 positive GM results of 70 patients. IA was identified in 29 patients (41.4%) (2 proven and 27 probable). For a single positive GMI of >0.5, >0.7, >1.0, and >1.5, the numbers were 104, 76, 57, and 32 and the positive predictive values (PPVs) were 39.4%, 43.2%, 47.2%, and 50.0%, respectively. The single GM positivity at different thresholds showed no difference between the IA and non-IA group ( P >0.05). For 2 consecutive positive GMI values of >0.5, >0.7, >1.0, and >1.5, the numbers were 34, 20, 13, and 4, and the PPVs were 58.8%, 65.0%, 84.6%, and 100.0%, respectively. In the IA group, positivity was higher at all thresholds ( P <0.05). According to our findings, consecutive GM positivity has higher PPVs independently from the cutoff value chosen. In pediatric patients with high risk, consecutive sampling should be preferred.